Incidental Verbal Semantic Processing Recruits the Fronto-temporal Semantic Control Network. (28th June 2021) - Jedidi, Z; Manard, M; Balteau, E; Degueldre, C; Luxen, A; Phillips, C; Collette, F; Maquet, P; Majerus, S
Abstract: The frontoparietal semantic network, encompassing the inferior frontal gyrus and the posterior middle temporal cortex, is considered to be involved in semantic control processes. The explicit versus implicit nature of these control processes remains however poorly understood. The present study examined this question by assessing regional brain responses to the semantic attributes of an unattended stream of auditory words while participants' top–down attentional control processes were absorbed by a demanding visual search task. Response selectivity to semantic aspects of verbal stimuli was assessed via a functional magnetic resonance imaging response adaptation paradigm. We observed that implicit semantic processing of an unattended verbal stream recruited not only unimodal and amodal cortices in posterior supporting semantic knowledge areas, but also inferior frontal and posterior middle temporal areas considered to be part of the semantic control network. These results indicate that frontotemporal semantic networks support incidental semantic (control) processes.